Antidepressant treatment for primary care patients with depressive symptoms: Data from the diamond longitudinal cohort study. (April 2020) - Davidson, Sandra K; Romaniuk, Helena; Chondros, Patty; Dowrick, Christopher; Pirkis, Jane; Herrman, Helen; Fletcher, Susan; Gunn, Jane
Background: In light of emerging evidence questioning the safety of antidepressants, it is timely to investigate the appropriateness of antidepressant prescribing. This study estimated the prevalence of possible over- and under-treatment with antidepressants among primary care attendees and investigated the factors associated with potentially inappropriate antidepressant use. Methods: In all, 789 adult primary care patients with depressive symptoms were recruited from 30 general practices in Victoria, Australia, in 2005 and followed up every 3 months in 2006 and annually from 2007 to 2011. For this study, we first assessed appropriateness of antidepressant use in 2007 at the 2-year follow-up to enable history of depression to be taken into account, providing 574 (73%) patients with five yearly assessments, resulting in a total of 2870 assessments. We estimated the prevalence of use of antidepressants according to the adapted National Institute for Health and Care Excellence guidelines and used regression analysis to identify factors associated with possible over- and under-treatment. Results: In 41% (243/586) of assessments where antidepressants were indicated according to adapted National Institute for Health and Care Excellence guidelines, patients reported not taking them. Conversely in a third (557/1711) of assessments where guideline criteria were unlikely to be met, participants reported antidepressant use. Being female and chronic physical illness were associated with antidepressant use where guideline criteria were not met, but no factors were associated with not taking antidepressants where guideline criteria were met. Conclusions: Much antidepressant treatment in general practice is for people with minimal or mild symptoms, while people with moderate or severe depressive symptoms may miss out. There is considerable scope for improving depression care through better allocation of antidepressant treatment.